Symbolism analysis using semiotic approach in Malaysian animated film - Imelda Ann Achin; Addley Bromeo Bianus (Academy of Arts and Creative Technology, UMS, 2022)
This study examines the symbolism in first anthropomorphic Malaysian animated film, Seefood. It aims to analyse the symbolism of animal characters as a visual metaphor in the Malaysian animated film. This paper is based on research using the Semiotic Saussure Theory in analysing the data. This paper records that cultural factors and knowledge of myths, beliefs and social differences as key aspects of symbolism application can be applied into new media, especially in the field of animation. This makes the character easier to attract the attention of the audience due to the existence of understanding and coherence of social cultural representations that are synonymous in the audience.